Immunology of the Lymphatic System - Santambrogio, Laura; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Immunology of the Lymphatic System is a comprehensive study of the lymphatic system and its immunological role. It begins with lymphatic capillaries, their origin and development. It addresses lymph circulation, in general, with a special emphasis on lymph circulation in parenchymal organs. The next section focuses on lymph nodes, subcortical circulation and the conduit system. It discusses organs with no lymphatic system, such as the brain. Finally, it covers lymph composition and cells in the lymph. While primarily basic research, the volume touches upon elements of the clinical, as well, broadening its scope and appeal.
Lymphatic Capillaries: Origin and Development -- Lymph Circulation -- Lymph Circulation in Parenchymal Organs -- Lymph in the LymphNodes Subcortical Circulation and the Conduit System -- Lymph in the Thymus -- Organs with No Lymphatic System (The Brain) -- Lymph Composition (The Omics) -- Cells in the Lymph.
Keywords: Immunology; Medical microbiology; Human physiology; Immunology; Medical Microbiology; Human Physiology